Freezing and melting of liquid droplets with suspended particles - Low, Victoria Cheng Han (Nanyang Technological University, 2021)
The freezing of water has always been a highly researched area in which the benefits of freezing water have numerous advantages and variabilities such as thermal energy storage methods and research on various anti-icing or de-icing methods. Nanofluids are another fluid that has been of high interest for many scientists in recent years due to the additional properties such as their thermal conductivity in comparison to using pure water. However, the melting dynamics of water and nanofluids have not been researched deeply and only in recent years did this research become more common. For this experiment, the nanofluid that would be used is titanium dioxide, a nanofluid that has very high thermal conductivity and high electrical stability. The focus of this research would be on the melting process of water and TiO2, observing the physical changes such as the size of the droplet and the melting interface. The timings of how long the melting process took and the melting speeds at different temperatures and volumes will also be recorded. To observe the melting process, the droplet must be frozen and therefore some observations of the freezing process will also be recorded. To conduct the experiment, a high-speed camera is used to capture the freezing and melting process, and the time that the droplet starts and ends melting is also recorded. The experiments are repeated multiple times to ensure repeatability and consistency in the results. Using the frames that were recorded, the size of the droplets and the freezing and the melting process can be observed frame by frame. There are results found that were expected from other research, however as this research paper covers parts that were not researched before, there were results that have not been found before. It was found that changes in volume do not affect the changes in melting time and pattern and the width of the frozen plateau. However, it was also found that after the freezing interface reaches the total height, it continues to increase in height upwards before the freezing finishes. Other results will be discussed in the report.